(3cJGH aj GdCOYjIs
(3ChdgG (B:s
(3TgGH Yf YQhI Yf YGFTI Cf GdfHi Udi Gddg Ydjg hSde cGf ZPG Chi Edi aQGTI cd djdg LeY cajg Ke faK ajgeG s
(3BNQgG (B:s
(3BNQ GdehLhO efg ai HGH GdOYGA Yf EaJJGM GdUdGI (B( (3Gddge Efi CYhP Hc ef GdTWGf hef geRg (B) s
(3fSNI YJjbIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdJUha hGdBOGH GdTQYjIs